2010
DOI: 10.1128/ec.00255-09
|View full text |Cite
|
Sign up to set email alerts
|

The Glycosylation Pathway of Eimeria tenella Is Upregulated during Gametocyte Development and May Play a Role in Oocyst Wall Formation

Abstract: Sexual-stage glycoproteins of Eimeria are important components of the oocyst wall, a structure that ensures the efficient transmission of these and related parasites. In this study, the primary enzyme in the glycosylation pathway of Eimeria tenella, glucosamine:fructose-6-phosphate aminotransferase (EtGFAT), has been characterized as a macrogamete-specific protein. Although the transcription of EtGFAT was observed early in macrogamete development, protein expression was restricted to mature macrogametes, prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
(47 reference statements)
0
17
0
Order By: Relevance
“…The transcription of genes encoding proteins with important roles in E. tenella gametocyte biology, including oocyst wall biosynthesis [ 16 ], protein glycosylation [ 17 ] and proteolytic cleavage of oocyst wall proteins [ 18 ], is typically restricted to gametocytes and zygotes (early oocysts). In order to identify other upregulated gametocyte transcripts, RNA Seq mapping was used to generate quantitative differential expression (DE) profiles of individual genes between developmental stages of E. tenella .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The transcription of genes encoding proteins with important roles in E. tenella gametocyte biology, including oocyst wall biosynthesis [ 16 ], protein glycosylation [ 17 ] and proteolytic cleavage of oocyst wall proteins [ 18 ], is typically restricted to gametocytes and zygotes (early oocysts). In order to identify other upregulated gametocyte transcripts, RNA Seq mapping was used to generate quantitative differential expression (DE) profiles of individual genes between developmental stages of E. tenella .…”
Section: Resultsmentioning
confidence: 99%
“…GAM56 and GAM82 have both been shown to be heavily glycosylated [ 35 ], a process that is linked to a co-regulated glycosylation pathway in Eimeria [ 17 ]. In the present study, six upregulated gametocyte transcripts were identified that code for enzymes in the protein glycosylation pathway, including EtGFAT (glucosamine: fructose-6-phophate aminotransferase) (ETH_00019125), the primary enzyme in the amino sugar biosynthesis pathway that was previously localised to E. tenella macrogametes [ 17 ]. Interestingly, recent studies have indicated the coccidian oocyst wall architecture is comprised not only of glycoproteins but also interlayered β-1,3-glucan fibrils [ 36 ] and an outer layer of acid-fast lipids [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Annotation of chromerids and colpodellids also reveals mucin proteins (for example Cvel_819. t1, Cvel_541.t1, and Colpodella_angusta_Spi-2_ cDNA_ca@a28207_52), as well as a conserved O-linked glycosylation machinery which was first described in coccidians (Templeton et al 2004b;Walker et al 2010). Our rough annotation of P. marinus indicates that it has perhaps an order of magnitude more genes which encode predicted mucins than Chromera, with potentially over 500 mucin genes within several families; based upon the features of predicted secretion, the presence of threonine repeats, and transmembrane or GPI-anchor domains.…”
Section: Introductionmentioning
confidence: 91%
“…RT-PCR was performed and the stage-specific cDNA samples were subjected to control PCRs to determine purity (Figure 1). Purification of merozoite and gametocyte lifecycle stages inevitably results in co-purification of host tissue, hence, the E. tenella β-actin structural gene was amplified to optimize relative amounts of parasite starting material as described previously [18]. The E. tenella β-actin gene was amplified from each of the parasite lifecycle cDNA samples and quantification of bands visualized by agarose gel electrophoresis allowed the specific E. tenella cDNA to be standardized to each other accordingly.…”
Section: Resultsmentioning
confidence: 99%